Kajian Emisi Kendaraan di Persimpangan Surabaya Tengah dan Timur serta Potensi Pengaruh terhadap Kesehatan Lingkungan Setempat - Handy Gunawan; Gogot Setyo Budi (Department of Urban and Regional Planning, Diponegoro University, 2017)
The growing number of motor vehicles on the street will increase the consumption of gasoline. At the national scale, gasoline consumption increased from 62.035.065 kiloliters in 2013 to 70.744.977 kiloliters in 2014. The increasing consumption of gasoline not only drains the non-renewable fossil energy but also affects the environment due to gas emission generated by fuel burning. The carbon monoxide (CO) or carbon dioxide (CO2), hydrocarbon (HC), nitrogen oxide (Nox), particulate matter (PM), and sulfide (SO2) concentration in a congestion area such as the area around traffic lights is substantially high. This research aims to find the gasoline consumption and emission rate in intersections with traffic lights, and its effect on surrounding environment. The research was done by collecting traffic volume in two locations in Surabaya, at morning rush hours, which started from 6.20 A.M. to 8.20 A.M, then calculated the emission rate and gasoline consumption from traffic data. The data showed that the volume of gasoline consumed in one lane (out of four lanes) at the traffic lights for two-hour duration was 700 liters, and the total substance of PM, NO, SO2 produced were 353 grams, 15.166 grams, and 410 grams. The concentration of NO and SO2 at Dr. Soetomo intersection after one-hour emission was 3059 μg/m3 and 57 μg/m3, while that at Kertajaya intersection was 672 μg/m3 and 12 μg/m3, respectively. These pollutants were away above the tolerable limit to human health as suggested by WHO, which should not exceed 50 μg/m3 for PM, 40 μg/m3 for NO3 for NO, and 20 μg/m3 for SO2.